2005
DOI: 10.5713/ajas.2005.384
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Rice Protein Concentrate on Growth Performance and Ileal Digestibility in Early-weaned Pigs

Abstract: These experiments were conducted to evaluate the feeding value of rice protein concentrate (RPC) in weaning pigs. In expt. I, a 5-week feeding trial was conducted with 126 pigs (L×Y×D; 21 d-old; 5.32±0.34 kg). Treatments were spray-dried plasma protein (SDPP; control), soy protein concentrate (SPC) and RPC (phase 1), and dried porcine soluble (DPS; control), SPC and RPC (phase 2). An ileal digestibility trial was also conducted to compare digestibility of amino acids in the tested protein sources. In expt. II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
12
3
Order By: Relevance
“…The SID in SBM hp , reported herein, are in good agreement with those reported by Yang et al (2007), whereas Walker et al (1986) reported up to 17 percentage units greater SID. For soy protein concentrate, reports on SID of indispensable AA vary between 94% and 100% (Walker et al, 1986) and between 81% and 91% (Yun et al, 2005;Yang et al, 2007). Moreover, Yun et al (2005) and Yang et al (2007) determined up to 6 percentage units smaller SID of indispensable AA in soy protein concentrate compared with the present study, whereas Walker et al (1986) reported up to 17 percentage units greater SID of indispensable AA in soy protein concentrate than the present study.…”
Section: Resultscontrasting
confidence: 54%
See 2 more Smart Citations
“…The SID in SBM hp , reported herein, are in good agreement with those reported by Yang et al (2007), whereas Walker et al (1986) reported up to 17 percentage units greater SID. For soy protein concentrate, reports on SID of indispensable AA vary between 94% and 100% (Walker et al, 1986) and between 81% and 91% (Yun et al, 2005;Yang et al, 2007). Moreover, Yun et al (2005) and Yang et al (2007) determined up to 6 percentage units smaller SID of indispensable AA in soy protein concentrate compared with the present study, whereas Walker et al (1986) reported up to 17 percentage units greater SID of indispensable AA in soy protein concentrate than the present study.…”
Section: Resultscontrasting
confidence: 54%
“…For soy protein concentrate, reports on SID of indispensable AA vary between 94% and 100% (Walker et al, 1986) and between 81% and 91% (Yun et al, 2005;Yang et al, 2007). Moreover, Yun et al (2005) and Yang et al (2007) determined up to 6 percentage units smaller SID of indispensable AA in soy protein concentrate compared with the present study, whereas Walker et al (1986) reported up to 17 percentage units greater SID of indispensable AA in soy protein concentrate than the present study. There is evidence, however, that the comparison of SID between the aforementioned studies and the present study may be confounded by methodological differences in the measurement of SID between these studies.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…2 Recent studies have demonstrated that RPC could replace soy protein concentrate (SPC) in a complex diet for prestarter pigs (7-35 days of age). 2 Palmegiano et al 3 used a similar RPC as substitute of fish meal in diets for freshwater and marine fish. However, little is known about the effect of RPC on the growth performance of early-weaned pigs (14-21days of age).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, rice protein concentrate (RPC), a much cheaper source of dietary protein, has become commercially available for use in the feed industry. 2 Feed grade RPC contains 63% crude protein and 2.423 MJ kg −1 ME (metabolism energy) for pigs.…”
Section: Introductionmentioning
confidence: 99%